PENINGKATAN KETERAMPILAN MENULIS TEKS PERSUASI DENGAN STRATEGI THINK TALK WRITE - Surani, Surani (Universitas Wijaya Kusuma Surabaya, 2021)
The problem that arises in this classroom action research is the low learning outcomes of Indonesian in the remaining class VIII of SMPN One Roof 3 clan Jaya. The purpose of this study was to determine the increase in Indonesian learning outcomes for students through the Improvement of Persuasion Text Writing Skills with the Think Talk Write Strategy for Class VIII Students of SMPN One Roof 3 Marga Jaya in the Academic Year 2020/2021. This classroom action research was conducted in two cycles, each cycle consisting of 4 stages, namely: planning, action, observation, and reflection. The method of collecting research data is through observation and tests. While the research indicator is KKM 72%. From the research results indicate an increase in student achievement. Based on the results of data analysis and discussion, it can be concluded that pre-cycle learning completeness by 72% increases to cycle I which reaches 82% means an increase of 9%. From cycle I to cycle II there was also an increase in learning completeness, namely from 82% in cycle I to 86% in cycle II. Thus, from the initial condition to the final condition, learning completeness has increased by 14%.